Rancang Bangun Aplikasi Tracking Paket Ekspedisi CV MK Express (Komputika : Jurnal Sistem Komputer, 2021)
Innovation is an effort done by an agencies or companies to improve the service quality so that they can survive in the current hypercompetition era. CV MK Express is a new company engaged in the service sector, particularly in the expedition service for goods and documents. As a newcomer company, CV MK Express innovates its service by creating a mobile-based application. This application includes a tracking system, picking-up and delivery of packages using GPS (Global Positioning System) feature. The package tracking system in this application is different from other similar applications because it uses a realtime tracking system, where users can see the presence point of packages per predetermined time interval. This study aims to design and build this application on the basis of mobile android. Android in this application is a hybrid type and was built using framework7, while the database used is MySQL. On the customer side, this research is expected to provide convenience service in making requests to pick-up and track the packages, while on the company side it is expected to expedite the business processes.Keywords - android hybrid, expedition, framework7, GPS (Global Positioning System), tracking system.